Construction of anisotropic fluorescent nanofibers assisted by electro-spinning and its optical sensing applications. Issue 22 (23rd April 2019) - Zhang, Fa-Heng; Jiang, Rui-Xue; Cao, Wei; Du, Bin; Cao, Ding-Yuan; Ding, Zhi-Jun; Li, Zhi-Jun
Abstract : Anisotropic fluorescent nanofibers constructed from the self-assembled perylene bisimide derivative and poly(vinylidene fluoride) show high sensitivity and short response time to aniline vapor. Abstract : Fixing the gap between "nano-scaled" pieces and "product-scale" materials, devices or machines is an ineluctable challenge that people have to tackle. Herein, we show that combining self-assembly and electrospinning processes results in the fabrication of anisotropic fluorescent nanofibers (PDI@PVDF ) in which the well-defined rod-like perylene bisimide derivative assemblies are embedded in a highly oriented way along the axis of the poly(vinylidene fluoride) (PVDF) fiber. Compared to fragile individualPDI assemblies, the electrospinning anisotropic fluorescentPDI@PVDF nanofibers not only maintain high sensitivity for aniline vapour but also exhibit an unexpected short response time for both quenching and recovering. The results demonstrate that electrospinning assistance is a versatile and effective strategy to maintain the anisotropy of fluorescent nanomaterials, building a bridge between self-assembled nano-rods and practical materials.